Architectural identity of Kampung Raja, Besut, Terengganu / Wan Hashimah Wan Ismail - Wan Ismail, Wan Hashimah (2012)
The paper discusses the search for the architectural identity of Kampung Raja, Besut, Terengganu. The paper is based on a research conducted in Kampung Raja involving site observation, literature review and interview of the residents. Measured drawings and documentations of 3 selected buildings were also executed. The research was focused on the built environment and the communities within the area from the Besut River to the main trunk road in Kampong Raja. This paper is elaborated in three sections. The first section is a discussion on issues relating to the identity of the place by referring to the opinion of the scholars. The second section concerns the historical background on the transformation of the area from a riverside settlement to a royal town and finally an administrative centre that make the place unique. The third section discusses the identity of the place by referring to the architectural styles of both the public and private buildings. On the whole, the findings of the research suggest that most f the new buildings within the area were designed according to the demands of the modern society but seem to be out of place. Some deeper understanding to the local architectural heritage is necessary in order to design new buildings that are sympathetic to the history and identity of the area.